PHYTOTESTING OF SOILS CONTAMINATED WITH OIL PRODUCTS UNDER CONDITIONS OF LONG-TERM POLLUTION: ON THE EXAMPLE OF BALYKCHY CITY (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
The search for express and reliable methods of assessing the ecological state ofecosystems polluted by xenobiotics is one of the most urgent tasks of scientists of ecologists.Phytotesting and phytoindication of contaminated ecosystems is one of the promising methodssatisfying the above requirements. Methods of phytotesting of soils contaminated with oil productsis an actual direction in the assessment and remediation of contaminated soils. One of the objectsof scientific interest is oil-contaminated soil in Balykchy city. As a result of leakage from the pipeof the oil depot in Balykchy, in the late 90s of the last century, about 600 tonnes of oil products gotinto the ground. The problem remains actual till today, as no effective measures on cleaning andrestoration of contaminated lands have been taken. It is of scientific interest to study and assessphytotoxicity of soils contaminated more than 30 years ago and to select optimal phytotest objects,both sensitive and resistant species.
Keywords: oil products, phytotest, microbiological method, soil, sustainable development